ENVIRONMENTAL ISSUE: BETWEEN SOCIAL DEMANDS AND FRAGMENTATION OF THE STATE RESPONSES - Alfaro Moscoso, Montserrat (2020)
This article is developed in the framework of a research project related to the main environmental demands placed on the Costa Rican public agenda, as well as the state responses between 1995-2015. The research was carried out through the review of hemerographic sources and the National Development Plans corresponding to the study period. As main results, eight topics were identified, positioned in the public discussion, and an important fragmentation of state responses in environmental matters is presented.